Novel procedure with improved resolution and specificity for amplification and differentiation of variants of the gene encoding carboxylesterase 1. Issue 4 (April 2017) - Bjerre, Ditte; Rasmussen, Henrik B.
Abstract : Carboxylesterase 1 (CES1) is implicated in the metabolism of several commonly used drugs and other xenobiotics. The gene encoding this enzyme, CES1, is duplicated in some individuals. The original gene copy is called CES1A1 . The duplicated version, CES1A2, is a hybrid of CES1A1 and the CES1 -related pseudogene, CES1P1 . Variants of CES1A2 with a weak and a strong promoter, respectively, have been reported. In addition, there are chimeric subtypes of CES1A1 that contain a segment of CES1P1 . Collectively, this represents challenges to the genotyping of CES1 that previous procedures have had difficulties in solving, frequently leading to loss of specificity and inaccurate genotyping. Here, we report a novel and specific procedure that can selectively amplify CES1A1 and CES1A2 and accurately determine their variants. This procedure may be useful for personalization of treatments with drugs metabolized by CES1. Abstract : Supplemental Digital Content is available in the text.